Pressão arterial média e o fluxo sangüíneo da artéria oftálmica externa em gatos (Felis catus Linnaeus, 1758) - Gonçalves, Gentil Ferreira (2005)
Veterinary medicine is benefitted by technological advances in diagnostic area by the spreading of scientific knowlagement. In order that new technologies may be used, information about normal standards for each type of examination is necessary, so that they may be used routinely and adequately prescribed for each patient. The Doppler ultrasound is beginning to be used in veterinary medicine for diverse purposes. The objectives of this study were to verify the Doppler ultrasound flow of the external ophthalmic artery in mixed breed cats anesthetized with tiletamine and zolazepam, and to correlate the average mean arterial pressure (MAP) surveyed by direct method in the same animals. There were used 20 mixed breed cats, both male and female, with body mass between 2 and 4 kilograms, proceeding from the Sociedade de Auxílio aos Animais de Umuarama - PR (SAAU). The animals received intra-muscular anesthesia with tiletamine and zolazepam (6,0 mg/kg). The femoral artery was assepticale cannulated and a manometer connected to an air column was connected to the catheter. The MAP was surveyed before and every 15 minutes until the end of the ultrasound examination. The flow of the external ophthalmic artery was measured through the ultrasond equipment Toshiba Powervision ATLHDI 3500, with an echo-doppler and a sectorial transducer of 6.0 MHz, directly applied to the cornea. Each eye had the artery flow surveyed by the equipment s own device, 3 samples being taken. The vascular resistance index was calculated based on the mean values of systolic and diastolic flow of each vasses. The values were tabulated and Student t test was applied to verify differences between the averages. Test of logistic regression was applied to the values of the MAP and the means of the artery flow to verify the correlation between the surveyed values. An average value for the MAP of 144.9 ± 26.68 mmHg and a flow of 14.28 ± 41.3 cm/sec for the external ophthalmic artery in the right eye in systole, 23.95 ± 11.46 cm/sec in diastole and 42.75 ± 12.64 cm/sec in the left eye in systole, 25.45 ± 9.61 cm/sec in diastole, were verified, there being no significant difference between the eyes. Correlation was not evidenced between the values of the MAP and the blood flow in the ophthalmic artery in both the eyes. The calculated index of vascular resistance was of 0.4175 ± 0.0774 for the external ophthalmic artery in the right eye and 0,4015 ± 0.0719 for the left eye, without any significant difference between the eyes. The results point to an intrinsic mechanism of flow control, controlled by local factors in the external ophthalmic artery. The values of the resistance index denote a low flow artery. Concluding, this study revealed the reference values, above cited, for the MAP and the blood flow in the external ophthalmic artery in mixed breed cats, anesthetized with tiletamine and zolazepam, and the information that there is no correlation between these values.